5.25.6 Problems 501 to 600

Table 5.1109: Second order, Linear, Homogeneous and constant coefficients

#

ODE

Mathematica

Maple

13441

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = 0 \]

13442

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

13443

\[ {}9 y^{\prime \prime }+6 y^{\prime }+5 y = 0 \]

13444

\[ {}4 y^{\prime \prime }+4 y^{\prime }+37 y = 0 \]

13646

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

13647

\[ {}y^{\prime \prime }+y^{\prime }-12 y = 0 \]

13649

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

13678

\[ {}y^{\prime \prime }+\lambda y = 0 \]

13679

\[ {}y^{\prime \prime }+\lambda y = 0 \]

13680

\[ {}y^{\prime \prime }+\lambda y = 0 \]

13681

\[ {}y^{\prime \prime }+\lambda y = 0 \]

13750

\[ {}x^{\prime \prime }-3 x^{\prime }+2 x = 0 \]

13751

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

13752

\[ {}z^{\prime \prime }-4 z^{\prime }+13 z = 0 \]

13753

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

13754

\[ {}y^{\prime \prime }-4 y^{\prime } = 0 \]

13755

\[ {}\theta ^{\prime \prime }+4 \theta = 0 \]

13756

\[ {}y^{\prime \prime }+2 y^{\prime }+10 y = 0 \]

13757

\[ {}2 z^{\prime \prime }+7 z^{\prime }-4 z = 0 \]

13758

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

13759

\[ {}x^{\prime \prime }+6 x^{\prime }+10 x = 0 \]

13760

\[ {}4 x^{\prime \prime }-20 x^{\prime }+21 x = 0 \]

13761

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 0 \]

13762

\[ {}y^{\prime \prime }-4 y = 0 \]

13763

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 0 \]

13764

\[ {}y^{\prime \prime }+\omega ^{2} y = 0 \]

13806

\[ {}a y^{\prime \prime }+\left (b -a \right ) y^{\prime }+c y = 0 \]

13980

\[ {}y^{\prime \prime }+4 y^{\prime }+y = 0 \]

13982

\[ {}2 y^{\prime \prime }-3 y^{\prime }-2 y = 0 \]

14019

\[ {}y^{\prime \prime }+9 y = 0 \]

14020

\[ {}4 y^{\prime \prime }-4 y^{\prime }+5 y = 0 \]

14021

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

14022

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = 0 \]

14023

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 0 \]

14024

\[ {}4 y^{\prime \prime }-4 y^{\prime }+37 y = 0 \]

14025

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 0 \]

14026

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

14027

\[ {}4 y^{\prime \prime }-12 y^{\prime }+13 y = 0 \]

14028

\[ {}y^{\prime \prime }+4 y^{\prime }+13 y = 0 \]

14029

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

14031

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 0 \]

14032

\[ {}y^{\prime \prime }-20 y^{\prime }+51 y = 0 \]

14033

\[ {}2 y^{\prime \prime }+3 y^{\prime }+y = 0 \]

14034

\[ {}3 y^{\prime \prime }+8 y^{\prime }-3 y = 0 \]

14035

\[ {}2 y^{\prime \prime }+20 y^{\prime }+51 y = 0 \]

14036

\[ {}4 y^{\prime \prime }+40 y^{\prime }+101 y = 0 \]

14037

\[ {}y^{\prime \prime }+6 y^{\prime }+34 y = 0 \]

14149

\[ {}y^{\prime \prime }+\alpha ^{2} y = 0 \]

14150

\[ {}y^{\prime \prime }-\alpha ^{2} y = 0 \]

14151

\[ {}y^{\prime \prime }+\beta y^{\prime }+\gamma y = 0 \]

14228

\[ {}y^{\prime \prime } = a^{2} y \]

14237

\[ {}y^{\prime \prime } = 9 y \]

14238

\[ {}y^{\prime \prime }+y = 0 \]

14239

\[ {}y^{\prime \prime }-y = 0 \]

14240

\[ {}y^{\prime \prime }+12 y = 7 y^{\prime } \]

14241

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

14242

\[ {}y^{\prime \prime }+2 y^{\prime }+10 y = 0 \]

14243

\[ {}y^{\prime \prime }+3 y^{\prime }-2 y = 0 \]

14244

\[ {}4 y^{\prime \prime }-12 y^{\prime }+9 y = 0 \]

14245

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

14267

\[ {}y^{\prime \prime }+2 h y^{\prime }+n^{2} y = 0 \]

14313

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

14323

\[ {}y^{\prime \prime }-3 y^{\prime }-10 y = 0 \]

14324

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

14335

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 0 \]

14337

\[ {}y^{\prime \prime }-y = 0 \]

14340

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

14341

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

14342

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

14343

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

14486

\[ {}y^{\prime \prime }-y = 0 \]

14487

\[ {}y^{\prime \prime }+y = 0 \]

14490

\[ {}y^{\prime \prime }-y = 0 \]

14496

\[ {}4 y^{\prime \prime }+4 y^{\prime }-3 y = 0 \]

14506

\[ {}y^{\prime \prime }+\alpha y = 0 \]

14522

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 0 \]

14539

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

14862

\[ {}y^{\prime \prime }-6 y^{\prime }-7 y = 0 \]

14863

\[ {}y^{\prime \prime }-y^{\prime }-12 y = 0 \]

14893

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 0 \]

14894

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

14895

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

14896

\[ {}y^{\prime \prime }+2 y = 0 \]

14975

\[ {}y^{\prime \prime }+16 y = 0 \]

14977

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

15211

\[ {}y^{\prime \prime } = y^{\prime } \]

15231

\[ {}y^{\prime \prime } = y^{\prime } \]

15245

\[ {}y^{\prime \prime } = y^{\prime } \]

15272

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

15273

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 0 \]

15280

\[ {}y^{\prime \prime }+y = 0 \]

15296

\[ {}y^{\prime \prime }+4 y = 0 \]

15297

\[ {}y^{\prime \prime }-4 y = 0 \]

15298

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 0 \]

15299

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

15309

\[ {}y^{\prime \prime }-4 y = 0 \]

15310

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = 0 \]

15311

\[ {}y^{\prime \prime }-10 y^{\prime }+9 y = 0 \]

15312

\[ {}y^{\prime \prime }+5 y^{\prime } = 0 \]

15315

\[ {}y^{\prime \prime }-7 y^{\prime }+10 y = 0 \]